National culture and innovation: a multidimensional analysis (INMR - Innovation & Management Review, 2023)
Purpose – This study aims to examine the relationships between the different national culture dimensionspresented by Hofstede and innovation data by country to analyze which characteristics of national culturedimensions contribute to the country becoming more innovative.Design/methodology/approach – The study is characterized as descriptive and quantitative, usingmultiple linear regression equations as data analysis technique. To carry out the analysis, this study made useof secondary data from Hofstede’s national culture database, data on innovation indicators from the GlobalInnovation Index and population data from the World Bank database. The analysis comprises data from 2015to 2018.Findings – National culture affects innovation rates positively. The most favorable situation to boostinnovation is when there is a low distance from power, high individualism, femininity characteristics, lowaversion to uncertainty, long-term orientation and a higher level of indulgence.Originality/value – The temporal analysis comprises a wider list of countries from all continents, whichhad not been considered in previous studies.